2014
DOI: 10.3402/gha.v7.25127
|View full text |Cite
|
Sign up to set email alerts
|

Sharing perspectives and experiences of doctoral fellows in the first cohort of Consortium for Advanced Research Training in Africa: 2011–2014

Abstract: BackgroundResolution of public health problems in Africa remains a challenge because of insufficient skilled human resource capacity. The Consortium for Advanced Research Training in Africa (CARTA) was established to enhance capacity in multi-disciplinary health research that will make a positive impact on population health in Africa.ObjectiveThe first cohort of the CARTA program describes their perspectives and experiences during the 4 years of fellowship and puts forward suggestions for future progress and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…This reflective approach demonstrates the experiential learning space at various levels as the capacity building process developed in commensurate ways among the individual post-docs, the CHESAI group and the affiliated organisations [38]. This form of reflective practice is not unique to this study but has also been used by the Consortium for Advanced Research Training in Africa on assessing African capacity building in health, whereas the experiential learning from the Malaria Capacity Development Consortium demonstrate the need to strengthen public health capacities for doctoral and post-doctoral programmes in Africa in general [39, 40]. …”
Section: Methodsmentioning
confidence: 99%
“…This reflective approach demonstrates the experiential learning space at various levels as the capacity building process developed in commensurate ways among the individual post-docs, the CHESAI group and the affiliated organisations [38]. This form of reflective practice is not unique to this study but has also been used by the Consortium for Advanced Research Training in Africa on assessing African capacity building in health, whereas the experiential learning from the Malaria Capacity Development Consortium demonstrate the need to strengthen public health capacities for doctoral and post-doctoral programmes in Africa in general [39, 40]. …”
Section: Methodsmentioning
confidence: 99%
“…The more senior group, who are attending their last JAS, interact with and peer-mentor those attending their first JAS. This is described in more detail elsewhere [2,14,15]. JAS sessions create formal and informal opportunities for fellows to cultivate interpersonal relationships.…”
Section: Design Of the Carta Programmentioning
confidence: 99%
“…The majority (61%) of the between-CARTA-fellows collaborative papers were produced during the doctoral intervention period. We also identified one publication which involved all fellows from one cohort describing their experience of CARTA [15], and one cross-cohort and cross-disciplinary collaborative paper which included a CARTA senior academic, describing the engagement between librarians brought together by CARTA [20].…”
Section: Patterns Of Collaboration In Carta Fellows' Publicationsmentioning
confidence: 99%
“…(Cohort 2 survey) Cohort 1 fellows confirmed that new methodological skills were learned and learning from each other was part of that process. 23 …”
Section: Phd Fellows' Experience Of Multidisciplinary Trainingmentioning
confidence: 99%